Allergenic Fungal Spores Diversity In The Air Of Dr.B.R.Ambedkar Open University, Telangana (Journal of Pharmaceutical Negative Results, 2023)
The main aim of the present study is to find out about allergenic fungal spores concentration in Dr.B.R.Ambedkar Open University, during the monsoon, pre-winter seasons of 2022 through the spider web analysis. Twelve allergenic fungal spores viz., Cladosporium sp., Alternaria sp., Ascospores , Ganoderma sp.,Dipolodia sp., Pithomyces sp., Curvularia sp.,Spegazzinia sp.,Coprinus sp.,Nigrospora sp.,Tetraploa sp.,Kretzschmaria sp.,which cause allergic rhinitis to human beings, were recorded from representing locality. Among the fungal diversity, Alternaria sp. (26.21%) was the most abundant fungal spore type, next predominant fungal spores were Curvularia sp. (22.65%).